Skeletal Muscle Injury and Repair: The Effect of Disuse and Denervation on Muscle and Clinical Relevance in Pedicled and Free Muscle Flaps - Kääriäinen, Minna; Kauhanen, Susanna (Journal of Reconstructive Microsurgery, 2012)
Skeletal muscle is prone to injury upon trauma or nerve damage. In reconstructive surgery, it is an interesting spare part. Fortunately, skeletal muscle is capable of extensive regeneration. Satellite cells, quiescent myogenic precursor cells, become activated following muscle injury: they divide and form myoblasts, fuse into myotubes, and finally mature to myofibers. Denervation in muscle or muscle flaps leads to myofiber atrophy, fibrosis, and fatty tissue infiltration. Experiments show that muscle flaps that are reinnervated also display a fair amount of atrophy. Muscle mass is better preserved after motor innervation than sensory innervation. Clinical data imply that innervation of the muscle flap does not improve volume preservation significantly compared with denervated flaps. In addition, the softness of the flap remains the same whether the flap is innervated or not. Innervation of the flap seems to be needed only if functional muscle reconstruction is the goal. If reinnervation is successful but the muscle is kept short, disuse atrophy will still proceed. Muscle flaps should therefore be placed into their original length.
Keywords: muscle injury; denervation; disuse; atrophy; flap